Effects of Mental And Physical Practice on Learning and Acquisition of a Hitting Skill - Noordin, Nooreen (1997)
This study examined the effectiveness of mental, physical, and mental-physical practice in the skill of hitting a ball off a batting tee and a ball thrown by a pitcher among upper secondary school students. A total of 59 subjects (n=59) were assigned into three groups, where each group underwent three stages of the experiment - 1) Pretest Stage, 2) Practice Stage, and 3) Post-test Stage. During the pre-test stage, perfonnance scores were taken for both skills. All groups did not receive any fonn of practice. The practice stage required each subject learning how to hit a ball off a batting tee correctly. Verbal and written instructions as well as a demonstration session were given on how to perform the skill. Scores were taken during the post-test stage as each subject hit ten legal balls thrown by a pitcher and another ten legal balls using the batting tee. Findings showed that subjects' who received physical practice and mental-physical practice improved significantly in their batting performance (batting tee). However, the mental practice group failed to show any significant improvement. As for their hitting perfonnance using a pitcher, subjects' who practiced physically failed to improve their performance results. In contrast, the mental practice and the mental-physical practice groups recorded significant changes in their performance scores. Analysis of covariance did show statistically significant differences in subjects hitting performance on both skills between the three groups. All three practice methods produced significant changes but the combined practice method proved most effective.